Pendampingan Pemadanan NIK dan NPWP bagi Wajib Pajak Orang Pribadi di Desa Nglembu - Made Laksi Sena Hartini; Lilik Rohmawati; Hetika; Alvionida Filda Sari Mareta; Hanifah Putri Tanty; Hanna Humaira (Yayasan Sumber Daya Manusia Cerdas, 2024)
The lack of public understanding regarding the alignment of the Population Identification Number (NIK) with the Taxpayer Identification Number (NPWP) is a major challenge in improving tax compliance in Indonesia. One of the areas facing this issue is Nglembu Village, Banyubiru District, Semarang Regency. This community service program aims to raise awareness and understanding of individual taxpayers regarding the alignment of NIK and NPWP through education and hands-on training. The methods used include field surveys for problem identification, the development of educational materials, and training with lectures and hands-on practice using the DJP Online platform. Socialization media such as leaflets, banners, and digital platforms were also utilized to extend the reach of education. The results showed active participation from 22 individual taxpayers, with a 90% improvement in understanding. Sixty percent of participants expressed an intention to report taxes regularly, and 80% stated they were able to update taxpayer data independently. In conclusion, the activity successfully improved taxpayers’ understanding and skills regarding the alignment of NIK and NPWP and can be replicated in other areas to enhance broader tax compliance.